Translating Action Research into Practice: Seeking Occupational Justice for People with Dementia. (June 2013) - O'Sullivan, Grace; Hocking, Clare
Dementia is a critical social issue that contributes to, and is exacerbated by, occupational deprivation. This article reports the findings of an action research project undertaken to explore the daily activities of people who live with dementia in the community. Data were gathered by interviews, observations, and focus groups in community settings. The process of data gathering and analysis were reciprocally integrated. The participants, 11 people with mild to moderate dementia and their primary caregiver, prioritized the need to change the way dementia is perceived. Their rationale included other people's understanding of dementia and the social isolation they experience, resulting from a decline in opportunities to engage in daily activities. Occupational therapists have a significant role to play, encouraging and supporting people who live with dementia to maintain health and well-being by participating in occupations. Overcoming systemic issues that create barriers to occupation is vital.